Resolution of Anterior Scleritis after Periodontal Therapy - Guncu, Guliz Nigar; Caglayan, Feriha (European Journal of Dentistry, 2011)
Scleritis is a chronic inflammation that involves the outermost coat and the skeleton of the eye. Scleritis may be associated with a systemic or immune mediated disease and it might be caused by an infection, trauma or drug reaction. This case presents a patient with generalized chronic periodontitis and anterior diffuse scleritis. A 30-year-old female complained of pain and persistent scleritis in the left eye was referred to the Periodontology department due to her periodontal problems. She was treated with oral non steroidal anti-inflammatory drugs and topical medications (corticosteroid) for her scleritis during last two years. However, these treatments failed to control the progression of the disease. After periodontal examination, deep periodontal pockets and serious bone loss was detected radiographically. She was treated by flap procedures and 3 teeth were extracted. After a 4-month healing period, scleritis was resulted in rapid resolution. (Eur J Dent 2011;5:337-339)
Keywords: Anterior scleritis; Periodontitis; Treatment